2014
DOI: 10.1024/0040-5930/a000496
|View full text |Cite
|
Sign up to set email alerts
|

Der Einsatz von Trinknahrung ist wirksam, zweckmäßig und wirtschaftlich

Abstract: Numerous studies have shown that medically indicated sip feeding is an effective and cost-saving mean to combat malnutrition. Particularly, acutely ill, elderly, polymorbid internal and surgical patients benefit from sip feeding. In Switzerland, the reimbursement of medically indicated sip feeding at home by the compulsory health insurance is critically important for the good of the patient and cost optimization. This is particularly true in the longer-term considering the demographic trends in Switzerland wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that sip feeding is an effective and cost-saving tool to combat malnutrition, particularly for acutely ill patients, elderly, and polymorbid patients (11). Observational studies show that 20-25% of patients are able to resume normal oral feeding when the feeding tubes are permanently removed (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sip feeding is an effective and cost-saving tool to combat malnutrition, particularly for acutely ill patients, elderly, and polymorbid patients (11). Observational studies show that 20-25% of patients are able to resume normal oral feeding when the feeding tubes are permanently removed (12,13).…”
Section: Introductionmentioning
confidence: 99%